2020
DOI: 10.1177/2380084419897614
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Patient Safety Culture in Dentistry

Abstract: Objectives: Medical errors are among the leading causes of death within the United States. Studies have shown that patients can be harmed while receiving care, sometimes resulting in permanent injury or, in extreme cases, death. To reduce the risk of patient safety incidents, it is imperative that a robust culture of safety be established. The primary objective of this study was to evaluate the patient safety culture among providers at 4 US dental institutions, comparing the results with their medical counterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 34 publications
0
26
0
7
Order By: Relevance
“…Literature indicates the use of different instruments for the evaluation of patient safety culture in dentistry 12,15,17,26 . Leong et al used “Hospital Survey on Patient Safety Culture” amongst dental students, staff, faculty and administrators in seven dental schools in the United States 15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature indicates the use of different instruments for the evaluation of patient safety culture in dentistry 12,15,17,26 . Leong et al used “Hospital Survey on Patient Safety Culture” amongst dental students, staff, faculty and administrators in seven dental schools in the United States 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Romani et al evaluated patient safety culture in three US dental schools using “Medical Office Survey on Patient Safety Culture” (MOSOPS) 26 . Recently, MOSOPS instrument was utilised by Yansane et al 17 to observe patient safety culture in three dental institutions in the United States. Both Romani et al and Yansane et al used MOSOPS amongst dental faculty, dental hygienists, dental students and dental staff 17,26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of this survey-based study also found that our medical colleagues appeared to be ahead in terms of patient safety culture. 12…”
Section: Potential For Over-regulationmentioning
confidence: 99%